Impacts of Responsive Loads and Energy Storage System on Frequency Response of a Multi-Machine Power System - Muhammad Saeed Uz Zaman; Raza Haider; Syed Basit Ali Bukhari; Hafiz Muhammad Ashraf; Chul-Hwan Kim (Machines, 2019)
In recent decades, the power grid’s configuration is shifting towards a smart grid where responsive loads and energy storage systems (ESS) are finding an increased role in the power system operation. In the presented work, a mathematical formulation for frequency response analysis of a multi-machine power system is developed, considering the individual and combined roles of ESS and responsive loads. The validity of the developed model is demonstrated with the help of multiple case studies, which consider the various configurations of the power system. Moreover, different combinations of capacities of generation units, ESS and responsive loads are also simulated. With the help of mathematical model and simulation results, it is demonstrated that ESS and responsive loads may improve the economy and performance of the power system even during the failure of a certain portion of generation capacity. Though the case studies consider non-reheat turbines only, the mathematical model and conclusions are equally valid for other types of turbines as well.